Oxidation mechanism of chlortetracycline in a membrane aerated biofilm reactor - Aydin, Ekrem; Erdem, Mehmet; Casey, Eoin; Hasar, Halil (Elsevier, 2021)
This study describes the oxidation of chlortetracycline (CTC) under nitrifying conditions in a membrane aerated biofilm reactor (MABR) in which microorganism uses O-2 as the electron acceptor and NH4+-N and CTC as the electron donors. The MABR was operated at various hydraulic retention time (HRTs), O-2 gas pressures and electron donors' loadings. The results showed that decreasing O-2 gas pressure and HRTs negatively influenced the removal of secondary electron donor (CTC) as it did not affect the removal of first electron donor (NH4+-N). The CTC flux reached particularly high values of up to 2.0 mg/m(2).d at O-2 pressures of 0.28 and 0.41 atm. Transformation products at very low concentrations and some low molecular weight fragmentation products with m/z ratio in the range of 64 and 408 were detected in the effluent. The carbon equivalents in the influent and effluent showed that a microbial oxidative degradation mechanism was responsible for the removal of CTC. Molecular community analysis revealed that the Betaproteobacteria bacterial group were dominant in the biofilm community for the oxidation of CTC. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Antibiotics degradation; Chlortetracycline oxidation; Transformation products; Membrane aerated biofilm reactor